2005
DOI: 10.1097/00042307-200501000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The association between lower urinary tract symptoms and sexual dysfunction: fact or fiction?

Abstract: In contrast to long-established opinion, an age-independent association between lower urinary tract symptoms and sexual dysfunction was found in several recent population-based trials. The nature of this association, however, remains unclear. Future study is required to gain a better understanding of the possible underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The lack of objective parameters of LUTS, such as uroflowmetry, is another limitation of this study, as we evaluated only the subjective parameter, IPSS. As LUTS and ED are believed to be linked, not only through pathological mechanisms but also in psychological aspects, 22 one hypothesis for interpreting these improvements is that the improved erectile function could have led to an improvement in the patient's quality of life, causing some confusion about the actual improvement of voiding symptoms. More evidence from clinical trials will be needed to clarify the relationships between the coadministration of both drugs and improvements in LUTS.…”
Section: Simultaneous Administration Of Udenafil and Anmentioning
confidence: 99%
“…The lack of objective parameters of LUTS, such as uroflowmetry, is another limitation of this study, as we evaluated only the subjective parameter, IPSS. As LUTS and ED are believed to be linked, not only through pathological mechanisms but also in psychological aspects, 22 one hypothesis for interpreting these improvements is that the improved erectile function could have led to an improvement in the patient's quality of life, causing some confusion about the actual improvement of voiding symptoms. More evidence from clinical trials will be needed to clarify the relationships between the coadministration of both drugs and improvements in LUTS.…”
Section: Simultaneous Administration Of Udenafil and Anmentioning
confidence: 99%
“…Population surveys have shown high levels of sexual dysfunction in men over the age of 50 years [1,2]. Recent evidences from both community and clinical trials have suggested a link between lower urinary tract symptoms (LUTS) and sexual dysfunction [3][4][5]. Transurethral resection of prostate (TURP), the standard surgical therapy for the relief of LUTS, is reported to cause sexual dysfunction as well.…”
Section: Introductionmentioning
confidence: 99%
“…Considering LUTS among the 46 enrolled patients, 35 patients had severe symptoms (IPSS score 19-35), and the other 11 patents had moderate symptoms (IPSS score [8][9][10][11][12][13][14][15][16][17][18][19]. With regard to subjective erectile function, 21 of the 46 patients had severe erectile dysfunction (ED) (IIEF-5 score less than 8), 5 had moderate ED (IIEF-5 score 8~11), 19 had mild ED (IIEF-5 score 12~21), and 1 had normal erectile function (IIEF-5 score more than 21).…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have suggested that BPH-related nocturia could be associated with erectile function [6,7], whereas there are opposite opinions [8,9]. With regard to the nocturia, nocturnal polyuria rather than benign prostatic obstruction (BPO) accounts for a greater proportion of nocturia [10].…”
Section: Introductionmentioning
confidence: 99%